Does access to free pre-kindergarten increase maternal labor supply? - Elias Ilin; Samantha Shampine; Ellyn Terry (Federal Reserve Bank of Atlanta, 2022)
In this paper, we evaluate the effects of free pre-kindergarten (pre-K) programs on the labor force participation (LFP) of mothers. We use variation in pre-K rules across all US states, including income eligibility requirements in some states. To estimate the causal effects of access to pre-K on labor supply, we exploit the panel aspect of the monthly Current Population Survey between 2002 and 2019. Specifically, we look at the change in labor market behavior of women when their child becomes age-eligible for pre-K, controlling for individual factors. We find that access to free pre-K programs increases overall maternal LFP by 2.3 percentage points. In particular, we find that mothers with the following demographic characteristics significantly increase their labor supply as a result of an access to free pre-K: married, college educated, residents of metropolitan areas, and with income either below 200 percent or above 400 percent of the federal poverty level. Our results are robust across a series of placebo tests and alternative specifications and sample restrictions.
Keywords: G50; H21; H23; I31; J01; J08; J15; J16; J18; J21; J22; 330; maternal labor force participation; childcare policies; universal pre-K; gender equality policies; early education policies